If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + 4 = 5y + -3 Reorder the terms: 4 + 6y = 5y + -3 Reorder the terms: 4 + 6y = -3 + 5y Solving 4 + 6y = -3 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. 4 + 6y + -5y = -3 + 5y + -5y Combine like terms: 6y + -5y = 1y 4 + 1y = -3 + 5y + -5y Combine like terms: 5y + -5y = 0 4 + 1y = -3 + 0 4 + 1y = -3 Add '-4' to each side of the equation. 4 + -4 + 1y = -3 + -4 Combine like terms: 4 + -4 = 0 0 + 1y = -3 + -4 1y = -3 + -4 Combine like terms: -3 + -4 = -7 1y = -7 Divide each side by '1'. y = -7 Simplifying y = -7
| 7x+4=2x+49 | | 7=(8x+5)+5 | | h+14=63 | | 223+334567.564383= | | r-15=16 | | 3y-10+y+54=8y+50-6y | | 5+2s+7=28 | | 12(80-x)=816 | | 2+5+x=3+4 | | 19-x-5=30 | | (25b-6)-8(3b+3)=-7 | | 8+3(-2n-7)=-(-5-3n) | | (x+4)(3x-24)=0 | | 7(b-5)=72 | | 18+-6g=-12g | | 3px(-3)=36 | | -2(-6x-4)=8x+2(x-2) | | 3(14+-5y)-5y=10 | | Y-15x=16 | | 2(1-x)+5=3(1+x)-8 | | -6(r+8)=-96 | | 5+3(-2g-7)=-40 | | -5-4p=27 | | y(2y+4)=77 | | x+15=65 | | -10-4p=22 | | 3x+5=6x-28 | | a-8=17 | | 45p+10q= | | 5(1+2p)=7p-1 | | -15-3p=6 | | 7+4b=4(1+b)+3 |